An interRAI derived frailty index predicts acute hospitalizations in older adults residing in retirement villages: A prospective cohort study. - Katherine Bloomfield; Zhenqiang Wu; Annie Tatton; Cheryl Calvert; Nancye Peel; Ruth Hubbard; Hamish Jamieson; Joanna Hikaka; Michal Boyd; Dale Bramley; Martin J Connolly (PLoS ONE)
Objectives The development of frailty tools from electronically recorded healthcare data allows frailty assessments to be routinely generated, potentially beneficial for individuals and healthcare providers. We wished to assess the predictive validity of a frailty index (FI) derived from interRAI Community Health Assessment (CHA) for outcomes in older adults residing in retirement villages (RVs), elsewhere called continuing care retirement communities. Design Prospective cohort study. Setting and participants 34 RVs across two district health boards in Auckland, Aotearoa New Zealand (NZ). 577 participants, mean age 81 years; 419 (73%) female; 410 (71%) NZ European, 147 (25%) other European, 8 Asian (1%), 7 Māori (1%), 1 Pasifika (<1%), 4 other (<1%). Methods interRAI-CHA FI tool was used to stratify participants into fit (0-0.12), mild (>0.12-0.24), moderate (>0.24-0.36) and severe (>0.36) frail groups at baseline (the latter two grouped due to low numbers of severely frail). Primary outcome was acute hospitalization; secondary outcomes included long-term care (LTC) entry and mortality. The relationship between frailty and outcomes were explored with multivariable Cox regression, estimating hazard ratios (HRs) and 95% confidence intervals (95%CIs). Results Over mean follow-up of 2.5 years, 33% (69/209) of fit, 58% (152/260) mildly frail and 79% (85/108) moderate-severely frail participants at baseline had at least one acute hospitalization. Compared to the fit group, significantly increased risk of acute hospitalization were identified in mildly frail (adjusted HR = 1.88, 95%CI = 1.41-2.51, p<0.001) and moderate-severely frail (adjusted HR = 3.52, 95%CI = 2.53-4.90, p<0.001) groups. Similar increased risk in moderate-severely frail participants was seen in LTC entry (adjusted HR = 5.60 95%CI = 2.47-12.72, p<0.001) and mortality (adjusted HR = 5.06, 95%CI = 1.71-15.02, p = 0.003). Conclusions and implications The FI derived from interRAI-CHA has robust predictive validity for acute hospitalization, LTC entry and mortality. This adds to the growing literature of use of interRAI tools in this way and may assist healthcare providers with rapid identification of frailty.